A Mirror of Rabbinic Hermeneutics - Veltri, Giuseppe (De Gruyter, 2015)
Rabbinic hermeneutics in ancient Judaism reflects this multifaceted world of the text and of reality, seen as a world of reference worth commentary. As a mirror, it includes this world but perhaps also falsifies reality, adapting it to one's own aims and necessities. It consists of four parts:Part I, considered as introduction, is the description of the
10.1515/9783110366419
Keywords: Hellenistisches Judentum; Judaism; Magie; Rabbinic literature; Rabbinische Literatur; Roman Religion; Römische Religion; Sprachtheorie; language theories; magic; RELIGION / Judaism / Sacred Writings